Fecal Microbiome Data Distinguish Liver Recipients With Normal and Abnormal Liver Function From Healthy Controls - Lu, Hai-Feng; Ren, Zhi-Gang; Li, Ang; Zhang, Hua; Xu, Shao-Yan; Jiang, Jian-Wen; Zhou, Lin; Ling, Qi; Wang, Bao-Hong; Cui, Guang-Ying; Chen, Xin-Hua; Zheng, Shu-Sen; et al. (Frontiers in Microbiology, 2019)
Emerging evidence suggests that altered intestinal microbiota plays an important role in the pathogenesis of many liver diseases, mainly by promoting inflammation via the “intestinal microbiota-immunity-liver” axis. We aimed to investigate the fecal microbiome of liver recipients with abnormal/normal liver function using 16S rRNA gene sequencing. Fecal samples were collected from 90 liver recipients (42 with abnormal liver function (Group LT_A) and 48 with normal liver function (Group LT_N)) and 61 age- and gender-matched healthy controls (HCs). Fecal microbiomes were analyzed for comparative composition, diversity, and richness of microbial communities. Principal coordinates analysis successfully distinguished the fecal microbiomes of recipients in Group LT_A from healthy subjects, with the significant decrease of fecal microbiome diversity in recipients in Group LT_A. Other than a higher relative abundance of opportunistic pathogens such as Klebsiella and Escherichia/Shigella in all liver recipients, the main difference in gut microbiome composition between liver recipients and HC was the lower relative abundance of beneficial butyrate-producing bacteria in the recipients. Importantly, we established a fecal microbiome index (specific alterations in Staphylococcus and Prevotella) that could be used to distinguish Group LT_A from Group LT_N, with an area under the receiver operating characteristic curve value of 0.801 and sensitivity and specificity values of 0.771 and 0.786, respectively. These findings revealed unique gut microbial characteristics of liver recipients with abnormal and normal liver functions, and identified fecal microbial risk indicators of abnormal liver function in liver recipients.